2018
DOI: 10.1177/0972262917750225
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Elements and Effects of 
Global Viral Advertising Content: 
A Cross-cultural Framework

Abstract: With advancements in information and communication technology, a lot of changes have come in the way the products are being promoted by the marketers across the globe. Viral marketing incites the consumers to disseminate marketing content through 
various modes and one of which includes viral advertisements. The study analysed the content of global advertisements to explore the dominating factors in the ad content which makes them viral across the globe. Survey was conducted online among the respondents of Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
(26 reference statements)
4
10
0
Order By: Relevance
“…Moran et al (2014) added that the message that generates by market or social by nature considered more believable and trustworthy than marketer-initiated messages. Sharma & Kaur (2018) who researched global advertising content to explore what factors made the viral content throughout the world, concluded that most of the global advertisements used transformational appeals with positive emotional content in the form of happiness, joy or gladness as the advertisement appeal strategy which then influence consumers intention to purchase and their viral intentions. The success of viral messages determined by entertainment, social needs, and consumer engagement (East et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moran et al (2014) added that the message that generates by market or social by nature considered more believable and trustworthy than marketer-initiated messages. Sharma & Kaur (2018) who researched global advertising content to explore what factors made the viral content throughout the world, concluded that most of the global advertisements used transformational appeals with positive emotional content in the form of happiness, joy or gladness as the advertisement appeal strategy which then influence consumers intention to purchase and their viral intentions. The success of viral messages determined by entertainment, social needs, and consumer engagement (East et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since the day it was born as a kind of email advertising in the beginning (Petrescu & Korgaonkar, 2011;Sharma & Kaur, 2018, viral advertising has made an indelible mark in the advertising industry (Phelps et al, 2004;Sharma & Kaur, 2018). Named in analogy to viruses due to their 'contagious' nature (Berger, 2013), viral advertising can be easily transmitted by and among the digital media users acting as 'disseminators' (Golan & Zaidner, 2008;Kaur et al, 2022;Miquel-Romero & Adame-Sánchez, 2013;Porter & Golan, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Named in analogy to viruses due to their 'contagious' nature (Berger, 2013), viral advertising can be easily transmitted by and among the digital media users acting as 'disseminators' (Golan & Zaidner, 2008;Kaur et al, 2022;Miquel-Romero & Adame-Sánchez, 2013;Porter & Golan, 2006). Defined as 'unpaid peer-to-peer communication of provocative content originating from an identified sponsor using the internet to persuade or influence an audience to pass along the content to others' (Porter & Golan, 2006, p. 29), viral advertising in turn attracts the attention of the advertisers because it can be cost-effective in this way without forcing the advertisers to make their ads reach more people (Çiftçi & Özdemir, 2022;Golan & Zaidner, 2008;Miquel-Romero & Adame-Sánchez, 2013;Phelps et al, 2004;Porter & Golan, 2006;Sharma & Kaur, 2018;Shirkhodaee & Rezaee, 2013). Furthermore, viral ads have the main function of brand-building (branding) rather than call to action and informing (Çiftçi & Özdemir, 2022;Golan & Zaidner, 2008;Ketelaar et al, 2016;Porter & Golan, 2006;Segev & Fernandes, 2022;Sharma & Kaur, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations